In-situ synchrotron characterisation of fracture initiation and propagation in shales during indentation. (15th January 2021) - Ma, Lin; Fauchille, Anne-Laure; Chandler, Michael R.; Dowey, Patrick; Taylor, Kevin G.; Mecklenburgh, Julian; Lee, Peter D.
Abstract: The feasibility and advantages of synchrotron imaging have been demonstrated to effectively characterise fracture initiation and propagation in shales during indentation tests. These include 1) fast (minute-scale) and high-resolution (μm-scale) imaging of fracture initiation, 2) concurrent spatial and temporal information (4D) about fracture development, 3) quantification and modelling of shale deformation prior to fracture. Imaging experiments were performed on four shale samples with different laminations and compositions in different orientations, representative of three key variables in shale microstructure. Fracture initiation and propagation were successfully captured in 3D over time, and strain maps were generated using digital volume correlation (DVC). Subsequently, post-experimental fracture geometries were characterised at nano-scale using complementary SEM imaging. Characterisation results highlight the influence of microstructural and anisotropy variations on the mechanical properties of shales. The fractures tend to kink at the interface of two different textures at both macroscale and microscale due to deformation incompatibility. The average composition appears to provide the major control on hardness and fracture initiation load; while the material texture and the orientation of the indentation to bedding combine to control the fracture propagation direction and geometry. This improved understanding of fracture development in shales is potentially significant in the clean energy applications. Highlights: In-situ synchrotron imaging is demonstrated to investigate fracturing in shales. 3D images were recorded during stepped loading and used to perform digital volume correlation. The deformation zones were quantitatively resolved. Composition, texture and orientation influence fracture initiation and propagation.